Management of Unstable Distal Radius Fractures: A Survey of Hand Surgeons - Salibian, Ara A.; Bruckman, Karl C.; Bekisz, Jonathan M.; Mirrer, Joshua; Thanik, Vishal D.; Hacquebord, Jacques H. (Journal of Wrist Surgery, 2019)
Background Length of immobilization after operative fixation of unstable distal radius fractures and management in elderly patients is an area of debate.Purpose The purpose of this study is to delineate common practices of fellowship-trained hand surgeons and how they compare with current evidence-based protocols.Methods Surveys were distributed to American Society for Surgery of the Hand members on preferred methods of fixation, postoperative immobilization, and variations in treatment of elderly patients with unstable distal radius fractures. Responses were analyzed in comparison to a literature review. Subgroups were compared with regard to training, practice type, and years in practice.Results Four-hundred eighty-five surveys were analyzed. Volar fixed-angle plating was the most common choice of fixation (84.7%). Patients are most often immobilized for 1 to 2 weeks (40.0%) with range of motion (ROM) therapy begun most commonly between 1 and 4 weeks (47.2%). The majority of surgeons do not treat fractures differently in patients more than 65 years old. Physicians with more than 20 years of experience were significantly more likely to begin wrist ROM sooner with volar plating versus other fixation techniques compared with physicians with less than 20 years of experience (40.7% vs. 34.2%, respectively). Also, physicians in academic-only practices were more likely to immobilize patients for a shorter time after volar plating compared with those in privademics.Conclusion Volar fixed-angle plating is the dominant fixation method for unstable distal radius fractures among fellowship-trained hand surgeons. Elderly patients are not treated more conservatively and rigid immobilization after operative fixation remains the treatment of choice despite current evidence-based protocols.
Keywords: distal radius fracture; fracture immobilization; volar plate; hand surgery; early mobilization